2013
DOI: 10.1007/s00894-012-1682-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing and modulating the intrinsic acidity of imidazole and pyrazole through beryllium bonds

Abstract: The structure and electronic properties of the complexes formed by the interaction of imidazole and pyrazole with different BeXH(BeX2) (X = H, Me, F, Cl) derivatives have been investigated via B3LYP/6-311+G(3df,2p)//B3LYP/6-31+G(d,p) calculations. The formation of these azole:BeXH(BeX2) complexes is accompanied by a dramatic enhancement of the intrinsic acidity of the azole, as the deprotonated azole is much more stable after the aforementioned interaction. Most importantly, the increase in acidity is so large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The reason behind this huge effect on the water acidity relies on the large binding energy differences between neutral and charged complexes. Previous works,,,,, have shown precisely that this binding enthalpy difference is related to the acidity enhancement through a thermodynamic cycle analogous to the one shown in Scheme .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The reason behind this huge effect on the water acidity relies on the large binding energy differences between neutral and charged complexes. Previous works,,,,, have shown precisely that this binding enthalpy difference is related to the acidity enhancement through a thermodynamic cycle analogous to the one shown in Scheme .…”
Section: Resultsmentioning
confidence: 82%
“…It is well‐known that in molecular clusters linked by hydrogen bonds, from dimers onwards, the thermodynamic acid‐base properties of the terminal monomers are substantially modified, as for instance in (HCN) n and (HNC) n . We have reported the possibility of modulating the acidity of imidazoles and pyrazoles by means of beryllium bonds; the huge acidity increases produced by alkaline‐earth bonds; the large proton affinity (PA) enhancements triggered by non‐covalent interactions; and the changes on the acidity and basicity of disiloxane due to the formation of complexes with Lewis acids and Lewis bases …”
Section: Introductionmentioning
confidence: 99%
“…36 Several examples of this kind were studied in detail by our group in recent years. [37][38][39][40][41] As a general rule, it has been observed that when a given compound forms a beryllium bond, the conjugated base becomes a much better electron donor than the acid from which it comes as compared with the same acid-base pair in absence of beryllium bonds, resulting in an acidity enhancement triggered by the beryllium bond. This acidity enhancement is the consequence of the significant amount of charge transferred from the Lewis base towards the available empty orbitals of the beryllium compound, accompanied, as explained in previous sections, by the corresponding deformation mainly of the BeX 2 subunit.…”
Section: Effects On the Intrinsic Properties Of The Interacting Monomersmentioning
confidence: 99%
“…Also of note is the work carried out by Marín‐Luna and co‐workers, who studied the effect of beryllium bonds on the tautomerism of two DNA bases, 9‐methylguanine and 1‐methylcytosine. Finally, a series of studies devoted to analysis of the interplay between beryllium bonds and other noncovalent forces should also be mentioned, highlighting the ability of beryllium bonds to act as efficient noncovalent regulators with beautiful and intelligent applications in fields such as molecular recognition and solid‐state chemistry.…”
Section: Introductionmentioning
confidence: 99%